A different sort of normal - Balfe, Abigail (Puffin, 2021)
The beautiful true story of one girl's journey growing up autistic - and the challenges she faced in the 'normal' world. I'm not like the other children in my class . . . and that's an actual scientific FACT My name is Abigail and I'm autistic. Unfortunately for younger me, I didn't know I was autistic until I was an adult person. This is my story of growing up navigating the confusing 'normal' world, all the while missing some Very Important Information. If you've ever felt different, out of place, like you don't fit in . . . then this book is for you. Told through the author's remarkable words, and just as remarkable illustrations, this is the book for those who've never felt quite right in the 'normal' world. It also challenges the commonly held views about autism, and shows just how much it can vary across the gender spectrum. Very important, very funny, and very informative, this is the book the world needs right now.